Rural area marginalisation: searching for tendencies. Case study: the Western fringes of Poland - Markuszewska, Iwona (Bulletin of Geography. Socio-economic Series, 2015)
The aim of this paper was to evaluate the intensity of rural area marginalisation. As a study region, Western periphery of Poland has been chosen. The spatial scope of the research covers three border voivodeships: Dolnośląskie, Lubuskie and Zachodniopomorskie, however, the study was conducted at the local level, including 310 rural and rural-urban gminas (administrative region of the 3rd order in Poland). The statistical data were derived from the Central Statistical Office from the period of last two decades. Results revealed the differences in the level of rural area marginalization and were analysed in terms of agricultural and socio-economic aspects.